STRATEGI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MEWUJUDKAN TRANSFORMASI DIGITAL DAN BUDAYA INOVASI DI LEMBAGA PENDIDIKAN - Ayi Najmul Hidayat; Sobari Sobari; Ade Hernawan (IKIP Siliwangi, 2026)
This research explores the life philosophy of the Miduana Indigenous community in Naringgul, Cianjur, as a form of enduring local wisdom. Through a qualitative case study, the research identifies how this community harmonizes Islamic teachings with ancestral Sundanese traditions. Key findings reveal that their